ORIGINS OF A MISTRUST: THE CHILEAN COMMUNIST PARTY FACES THE NATIONALIST REVOLUTIONARY MOVEMENT AND THE DICTATORSHIP OF VILLARROEL IN BOLIVIA (1943-1946) - Fernández Abara, Joaquín (Revista de Historia Social y de las Mentalidades, 2024)
The article discusses the interpretation of the Chilean Communist Party on the Dictatorship of Gualberto Villarroel in Bolivia and performance that had in it the Revolutionary Nationalist Movement, between 1943 and 1946. The author argues that this interpretation was marked by anti-fascism and an interpretation of Bolivian history influenced by liberal platitudes. Thus, nationalism MNR and the Bolivian military was depicted as a form of fascism and his role in the Latin American context was analyzed under a panamerican perspective, considering it as part of a plan of the Axis to hinder the work of the Allies in America. In this line, the Chilean Communists fought for the Chilean Foreign Ministry denied recognition to the Bolivian government and entered into conflict with political and union actors prone to recognition of the Bolivian Dictatorship.